Secret key cryptography : ciphers, from simple to unbreakable - Rubin, Frank (Cryptographer) (Manning Publications Co., 2022)
Explore the fascinating and rich world of Secret Key cryptography! This book provides practical methods for encrypting messages, an interesting and entertaining historical perspective, and an incredible collection of ciphers and codes--including 30 unbreakable methods. In Secret Key Cryptography: Ciphers, from simple to unbreakable you will: Measure the strength of your ciphers and learn how to guarantee their security Construct and incorporate data-compression codes Generate true random numbers in bulk Construct huge primes and safe primes Add an undetectable backdoor to a cipher Defeat hypothetical ultracomputers that could be developed decades from now Construct 30 unbreakable ciphers Secret Key Cryptography gives you a toolbox of cryptographic techniques and Secret Key methods. The book's simple, non-technical language is easy to understand and accessible for any reader, even without the advanced mathematics normally required for cryptography. You'll learn how to create and solve ciphers, as well as how to measure their strength. As you go, you'll explore both historic ciphers and groundbreaking new approaches--including a never-before-seen way to implement the uncrackable One-Time Pad algorithm. Whoever you are, this book is for you! History buffs will love seeing the evolution of sophisticated cryptographic methods, hobbyists will get a gentle introduction to cryptography, and engineers and computer scientists will learn the principles of constructing secure ciphers. Even professional cryptographers will find a range of new methods and concepts never published before. About the Technology From the Roman empire's Caesar cipher to the WWII Enigma machine, secret messages have influenced the course of history. Today, Secret Key cryptography is the backbone of all modern computing infrastructure. Properly designed, these algorithms are efficient and practical. Some are actually unbreakable, even using supercomputers or quantum technology! About the Book Secret Key Cryptography teaches you how to create Secret Key ciphers, ranging from simple pen-and-paper methods to advanced techniques used in modern computer-based cryptography. It reveals both historic examples and current innovations. You'll learn how to efficiently encrypt large files with fast stream ciphers, discover alternatives to AES encryption, and avoid strong-looking but weak ciphers. Simple language and fun-to-solve mini-ciphers make learning serious concepts easy and engaging. What's Inside Construct 30 unbreakable ciphers Measure the strength of your ciphers and guarantee their security Add an undetectable backdoor to a cipher Defeat hypothetical ultracomputers of the future About the Reader For professional engineers, computer scientists, and cryptography hobbyists. No advanced math knowledge is required. About the Author Frank Rubin has been doing cryptography for over 50 years. He holds an MS in Mathematics, and a PhD in Computer Science. Quotes With the depth and breadth of knowledge in these pages, no one is more capable of enlightening a reader in classical cryptology than Dr. Frank Rubin. - From the Foreword by Randall K. Nichols, former president of the American Cryptogram Association Unleash your inner secret agent as you understand, design, and create world-class ciphers. This book is all you need. - Roy Prins, Salesforce It's no secret! This book is the key to unlocking the world of cryptography. - Chris Kardell, FIS Fantastic! Covers the history and the techniques of cryptography in a way I never thought I needed--until I read this book! - Matthew Harvell, AbacusNext.